Characteristics and Outcomes of Blood Product Transfusion During Critical Care Transport. (2nd September 2016) - Mena-Munoz, Jorge; Srivastava, Udayan; Martin-Gill, Christian; Suffoletto, Brian; Callaway, Clifton W.; Guyette, Francis X.
Abstract: Background: Civilian out-of-hospital transfusions have not been adequately studied. This study seeks to characterize patients receiving out-of-hospital blood product transfusion during critical care transport.Study Design and Methods: We studied patients transported by a regional critical care air-medical service who received blood products during transport. This service carries two units of uncrossmatched packed Red Blood Cells (pRBCs) on every transport in addition to blood obtained from referring facilities. The pRBC are administered according to a protocol for the treatment of hemorrhagic shock or based on medical command physician order. Transfusion amount was categorized into three groups based on the volume transfused (<350 mL, 350–700 mL, >700 mL). The association between prehospital transfusion and in-hospital outcomes (mortality, subsequent blood transfusion and emergent surgery) was estimated using logistic regression models, controlling for age, first systolic blood pressure, first heart rate, Glasgow Coma Score, time of transfer, and length of hospital admission.Results: Among the 1, 440 critical care transports with transfusions examined, 81% were for medical patients, being gastrointestinal hemorrhage the most common indication (26%, CI 24–28%). pRBC transfusions were associated with emergent surgery (OR = 1.81, 95% CI = 1.31–2.52) and in-hospital transfusions (OR = 2.00, 95% CI = 1.46–2.76). Those with transfusions >700 mL were associated with emergent surgery (OR = 1.79, 95% CI = 1.10–2.92) and mortality (OR = 2.11; 95% CI = 1.21–3.69).Conclusions: In this sample, the majority of patients receiving blood products during air-medical transport were transfused for medic conditions; gastrointestinal hemorrhage was the most common chief complaint. The pRBC transfusions were associated with emergent surgery and in-hospital transfusion. Transfusions of >700 mL were associated with mortality.